Simulation and modeling of mixture formation under variant ambient condition and injection pressure of biodiesel spray - Andsaler, Adiba Rhaodah; Khalid, Amir; Jaat, Norrizam (Penerbit UTHM, 2017)
This study focuses on determining the characteristics of the spray produced in the simulation of spray biodiesel using constant volume chamber by using computational fluid dynamic (CFD). The parameters investigated, including spray angle, spray penetration and area of spray. It uses biodiesel as fuel combustion in the constant volume chamber. The simulation was performed at different ambient pressure and temperature. The ambient pressure was varied at 2 MPa, 3 MPa and 4 MPa. While at ambient temperature was varied at 750 K, 850 K and 950 K. Result shows when in high ambient pressure, the spray of biodiesel angle increased. The results also indicated that, the length of the spray and spray area decreased as increasing in the ambient temperature. The increase in ambient temperature caused a high rate of evaporation of fuel in the constant volume chamber.